Determination of the optimum environmental requirements of juvenile marine fish : the development of a protocol - Deacon, Neil (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1997)
The spotted grunter, Pomodasys commersonnii, has been identified as a candidate species for mariculture in South Africa due to its high market demand and apparent biological suitability for culture. In common with most other potential mariculture species the spotted grunter has an estuarine juvenile phase. In this respect, the difficulties encountered in determining the optimum environmental requirements of spotted grunter are applicable to the majority of other potential mariculture species. Due the variability of estuarine habitats determination of the optimum environmental requirements of estuarine species under laboratory conditions are a prerequisite to subsequent evaluation of aquaculture potential. Therefore, using the spotted grunter as a representative of a typical potent ial mariculture species, the aim of this study was to contribute to the protocol for evaluating the environmental requirements of potential aquaculture species. The growth of fish is dependent on the relationship between food intake, metabolism and environmental factors. In this relationship, environmental factors do not act on growth per se, but rather act through metabolism on growth. Consequently, the environmental factors affecting the growth of a fish species can be classified into functional categories according to their respective influence on metabolic processes. Five functional categories are recognised, namely: controlling, limiting, masking, directive and lethal factors. In this study, the functional categories were sequenced to develop a theoretical protocol for determining the optimum environmental requirements of potential mariculture species under artificial conditions. It was hypothesised that the correct sequence for experimentally determining the optimum environmental requirements of a species should correspond to theoretical protocol. The hypothesis was tested from the experimental investigation into the individual effects of temperature, salinity, light intensity, photoperiod and food intake on growth performance of juvenile spotted grunter. The investigations quantified the relative effects of controlling, masking, directive and limiting factors on growth performance. The results of the studies were statistically compared to obtain a ranking of the effects of the environmental factors (e.g. temperature, salinity, etc.) on growth performance of juvenile spotted grunter. The statistical ranking facilitated the formulation of a second protocol for sequentially determining the optimum environmental requirements of a species. The second protocol was derived purely from the experimental data. Based on the corroboration between the theoretical protocol and that formulated from the experimental investigations, the hypothesis was accepted. Confirmation of the protocol for examining the effects of controlling, limiting, masking and directive factors provided a basis for the development of a preliminary experimental sequence for determining the optimum environmental requirements of juvenile marine fish. In the development of the experimental sequence, the protocol was interpreted in conjunction with the experimental methods used to determine the effects of environmental factors on the growth of juvenile spotted grunter. The experimental sequence provides a logical frame work within which the optimum environmental requirements of other marine fish species can be determined. In addition, evaluation of growth performance by this method provides a basis for comparison of the mariculture potential between species.
Keywords: Mariculture Fishes -- Ecology; Grunts (Fishes) -- Ecology; Pomadasys -- Ecology